Health literacy mediates the relationships of cognitive and physical functions with health-related quality of life in older adults - Chow, Bik C.; Jiao, Jiao; Duong, Tuyen V.; Hassel, Holger; Kwok, Timothy C. Y.; Nguyen, Minh H.; Liu, Huaxuan (Frontiers in Public Health, 2024)
Background: Declining cognitive function (CF) and physical function (PF) relate to poorer health-related quality of life (HRQoL) in older adults. As health literacy (HL) facilitates health information utilization, it may mediate links between functionality and HRQoL appraisals. This study examined HL as an intermediary between joint CF and PF contributions and HRQoL in Hong Kong older adults. Methods: 490 older adults aged 50-80 years completed assessments from March to July 2021. Health Literacy Survey Questionnaire Short Form 12 questions (HLS-SF12), Montreal Cognitive Assessment (MoCA), Senior Fitness Test (SFT) and 12-Item Short-Form Health Survey version 2 (SF-12v2) were used to assess HL, CF, PF and HRQoL, respectively. Path analysis tested a model with HL mediating CF/PF predictors and HRQoL outcome. Results: Results for direct effects indicated that CF significantly associated with PF (β=.115, SE=.012, P <.001), PF significantly connected to HL (β=.101, SE=.022, P<.001), and HL significantly related to HRQoL (β=.457, SE=.049, P<.001). Meanwhile, PF significantly linked to HRQoL directly (β=.156, SE=.025, P<.001) as well as indirectly (β=.046, 95% CI [.028, .067]). Significant mediating effect of HL was found on the relationship of PF and HRQoL. Conclusion: Findings confirm CF and PF joint impacts on HL and HRQoL in older adults, elucidating HL's mediating role in translating functionality levels into HRQoL. Fostering enduring health knowledge access may thus buffer effects of age-related declines on well-being. Results can inform interventions leveraging this pathway to promote resilient trajectories.